Grief, Tragic Death, and Multiple Loss in the Lives of Irish Traveller Community Health Workers. (May 2020) - Tobin, Mary; Lambert, Sharon; McCarthy, John
Recent data on the inequities in mortality, health, and access to health services experienced by the Traveller community in Ireland show higher rates of death by suicide and other sudden causes among members of this marginalized minority group than in the general population. Psychological literature on bereavement suggests that traumatic deaths and multiple deaths within a close network may be more likely to lead to complicated grief reactions. The aim of this study is to add to our understanding of the effects of the differential mortality rate by exploring how grief is experienced within the Traveller community in the context of bereavement from multiple deaths or sudden deaths (including suicide). Data from three semistructured focus group interviews with a total of 10 Traveller Community Health Worker participants (nine female and one male) were analyzed using Interpretative Phenomenological Analysis. Two master themes organized the salient phenomenological aspects of the grief experience: Living with Tragic Loss and Communicating Tragic Loss. A picture emerged of individual and community-level loss that is extensive, profound, and enduring. The sequelae of deaths by suicide include difficulties in coping, a search for meaning, and a pervasive sense of fear. Silence, the embodied act of giving voice to tragic loss, and strategies for managing disclosure of tragic deaths with children were all strong themes which emerged from the analysis. This study uses interpretative phenomenological analysis to generate a vivid picture of the lived psychological experience of grief as it is experienced by members of a minority group with above average rates of sudden and early deaths. This contributes to understanding the burden of health inequality in an underresearched population. Findings in relation to challenges in communicating with children about tragic deaths can be integrated into bereavement support resources.